Nitric oxide promotes cysteine N-degron proteolysis through control of oxygen availability - Haeun Kim; Ya-Min Tian; Peter J. Ratcliffe; Thomas P. Keeley (Proceedings of the National Academy of Sciences, 2025)
Selected proteins containing an N-terminal cysteine (Nt-Cys) are subjected to rapid, O 2 -dependent proteolysis via the Cys/Arg-branch of the N-degron pathway. Cysteine dioxygenation is catalyzed in mammalian cells by 2-aminoethanethiol dioxygenase (ADO), an enzyme that manifests extreme O 2 sensitivity. The canonical substrates of this pathway in mammalia are the regulators of G-protein signaling 4, 5, and 16, as well as interleukin-32. In addition to operating as an O 2 -sensing mechanism, this pathway has previously been described as a sensor of nitric oxide (NO), with robust effects on substrate stability upon modulation of NO bioavailability being widely demonstrated. Despite this, no mechanism to describe the action of NO on the Cys/Arg N-degron pathway has yet been substantiated. We demonstrate that NO can regulate the stability of Cys N-degron substrates indirectly via the regulation of ADO cosubstrate availability. Through competitive, O 2 -dependent inhibition of cytochrome C oxidase, NO can substantially modify cellular O 2 consumption rate and, in doing so, alter the availability of O 2 for Nt-Cys dioxygenation. We show that this increase in O 2 availability in response to NO exposure is sufficient to alter both dynamic and steady-state ADO substrate levels. It is likely that this mechanism operates to couple O 2 supply and mitochondrial respiration with responses to G-protein-coupled receptor stimulation.